Propuesta escultórica de la figura estilizada femenina realizada en madera - Cardenas Santin, Maria Fernanda (2018)
The present research has as theoretical support the analysis of the stylization of the female human figure in modern times, to arrive at a synthesis that will allow the accomplishment of the sculptural work taking wood as raw material. For this reason, the characteristics and artistic techniques of the sculpture in wood will be analyzed to make a sculptural proposal directed to the carving in wood taking as referents to the artists Henry Moore and Dame Barbara Hepworth with whom a test of the proposed sculptural work will be realized. To obtain information was used as a field instrument the observation, experimentation and collection of data, bibliographical, photographic, and technological means. It will analyze the history of sculptural trends and their main exponents, and the explanation of the process to raise it. The present work will be supported by the inductive method that will allow starting from the analysis of the female human figure until a synthesis can be reached that bases the sculptural proposal from the personal vision.